Socialization of Pawnship Law (RAHN) From an Islamic Perspective for Teachers of the El Fajr Foundation in Palembang - Bagus Setiawan; Ria Astina; Cindi Pramita (Multidisiplin Pengabdian Kepada Masyarakat, 2026)
Pawning is a form of muamalah transaction frequently used by people to meet economic needs. In Islam, pawning is known as rahn and is permitted as long as it meets the principles of justice and does not contain elements of usury. However, many people, including teachers, still do not fully understand the concept and legal provisions of pawning from an Islamic perspective. This community service activity aims to improve the understanding of teachers at the El Fajr Foundation in Palembang regarding pawning law (rahn) based on sharia principles. The methods used included outreach, lectures, discussions, and a question-and-answer session. The results of the activity showed an increase in participants' knowledge regarding the concept of rahn, the legal basis of pawning in Islam, and the differences between conventional pawning and sharia pawning. This activity is expected to increase Islamic economic legal literacy and encourage the implementation of muamalah practices in accordance with sharia values.